The Development of an Android Application: The Effects of Health Education Delivery through the Application in Caring for Islamic Preterm Infants after Discharge from a Hospital - Hayeese, Wanisa; Chaimongkol, Nujjaree; Sriyasak, Atcharawadee; Yeepaloh, Mayuree (Princess of Naradhiwas University Journal, 2021)
This research and development aimed to develop and determine the effects of health education delivery through an application in caring for Islamic preterm infants after discharge from a hospital. The study employed four stages: (1) Situation analysis and need assessment which the informants were 15 persons including professional nurses and mothers of preterm infants. Content analysis was used for data analysis; (2) Design content platform and development of knowledge and health education on android application were developed by researchers and was validated by experts; (3) Trying out and feasibility testing of the content application were done with 27 mothers of preterm infants. A questionnaire of knowledge pretest and posttest about caring for preterm infants in Muslim way was used through android application. Data were analyzed by t-test and (4) Evaluation and modification pattern were collected data from 10 professional nurses and 27 mothers of preterm infants, who accessed and used the developed application. Research instruments for data collection were questionnaires of a demographic and the satisfaction of using the application for health education delivery. Data were analyzed by using frequency, percentage, mean and standard deviation The results revealed that (1) The new health education delivery through the application in caring for Islamic preterm infants after discharge from a hospital consisted of caring for preterm infants to be a complete Muslim, caring for preterm infants to health problems, caring for preterm infants to halal and health nutrition and caring for preterm infants ties to god, (2) After receiving health education delivery through the application, the mothers had significantly more knowledge than before receiving (t = 17.24, P<0.01) and (3) The nurses and the mothers of preterm infants were satisfied with the health education delivery through the developed application with high total mean scores (M = 4.39, S.D. = 0.44 and M = 4.40, S.D. = 0.53, respectively). These findings suggest that healthcare providers should utilize this android application to deliver health education, which is convenient, easy, modern and in trend. Moreover, the mothers could repeatedly learn by themselves. Nurses and mothers of preterm infants could also utilize this application in caring for Islamic preterm infants.